Contributo alla conoscenza di Nora in età tardo-antica: il contesto ceramico dell’ambiente ipogeo o 'vano G' - Napolitano, Miriam (Rei Cretariae Romanae Fautorum Acta, 2022)
The city of Nora, located on the southern coast of Sardinia, represents an important field of study for the understanding of continuity and discontinuity in terms of the historical, political and cultural changes which occurred between the Phoenician age and the Byzantine era. Since 2016 the University of Cagliari has carried out archaeological investigations in the former military area in order to identify a new residential area, probably built between the 1st century BC and the 1st century AD. The whole area was frequented possibly until the 8th century AD when the city was abandoned. This essay aims to analyse the ceramics found in the fill of an underground cistern ‘G’ in order to determine the terminal date of its filling, an event which is thought to have occurred during the 6th century AD. The proofs of this chronological hypothesis are represented by interesting ceramic markers mainly respecting plain and coarse wares which occur also in the North African area, in Sicily and in local productions. This evidence provides a useful account of how the commercial flows between Nora and the other provinces of the Mediterranean basin were organised during the last centuries (6th – 8th century AD) of its existence.